Enhancing antibacterial efficacy and accelerating infectious wound healing in rats using biogenic metal nanoparticles from marine Bacillus subtilis - Pemmadi, Raghuveer Varma; Alhakamy, Nabil Abdulhafiz; Asfour, Hani Z.; Kotta, Sabna; Alfaleh, Mohamed A.; Sunnapu, Prasad; Uk, Ilyas; Pottail, Lalitha; Chithambharan, Akhila; Yogananthan, Dhanapal; Thavamani B, Samuel; Valiyaparambil, Shilpa; et al. (Frontiers in Marine Science, 2024)
Cell-free aqueous extracts of marine Bacillus subtilis (CBPPR1) were used to synthesise AuNPs (CBPPR1AuNPs) and AgNPs (CBPPR1AgNPs). Zetasizer Nano ZS (Malvern Instruments) zeta size and zeta potential, field emission and transmission scanning electron microscopy (FE-SEM and HR-TEM), UV-visible (UV-Vis), X-ray diffraction (XRD), Fourier transform infrared (FT-IR), and EDAX were used to characterize biogenically synthesized nanoparticles (NPs). Their antibacterial activities against Escherichia coli, Klebsiella pneumoniae, and Staphylococcus aureus were investigated. The anticancer efficacy of CBPPR1Au and AgNPs was investigated in human colorectal adenocarcinoma cell lines (HT-29, HT-116). CBPPR1AgNPs formulation was studied in vitro and in-vivo rat models. The assessment focused on its efficacy in wound healing and antibacterial capabilities, comparing them against a commercial product. To determine the effectiveness of CBPPR1AgNPs in wound healing, a cutaneous wound model was employed, which included infection with S.aureus. CBPPR1Au and AgNPs significantly inhibited the growth of S aureus at MIC of 125 µg (CBPPR1AuNPs) and 62.5 µg (CBPPR1AgNPs) respectively. FE-SEM and HR-TEM observations confirmed that NPs caused bacterial cell leakage, damage, and shrinkage. Cancer cell viability was reduced upon treatment with increasing concentrations of CBPPR1Au and AgNPs, and apoptosis was increased in cells treated with CBPPR1Au and AgNPs relative to untreated cells (p < 0.001). CBPPR1Au and AgNPs showed significant cytotoxic activity against HT-29 (15.5 M) and HT-116 (62.5 M) cells. In-vivo experiments on rats showed minimal pus formation in groups CBPPR1AgNPs (62.5 µg/ml) G2, CBPPR1AgNPs (125 µg/ml) G3, and silver sulfadiazine G4, indicating the effective control of infections.CBPPR1AgNPs-treated wounds showed complete closure, whereas untreated G1 wounds remained unhealed. Histopathological analysis showed no adverse effects of CBPPR1AgNPs on kidneys and livers of rats. These findings suggest that CBPPR1AgNPs play a pivotal role in wound healing because of their potent antibacterial properties.